A continuum of hate: delimiting the field of hate studies - Schweppe, Jennifer (Crime, law and social change, 2022)
A relatively nascent discipline, the field of hate studies has been explored and theorised from a multiplicity of disciplinary contexts. However, the field is ill-defined, and the relationship between hate crime and other related concepts unexplored. Here, we consider the range of phenomena which might fall within or without the field of hate studies, initiating a discussion of the boundaries of the field. We signal both the continuities and discontinuities among and between an array of strategies intended to sort and maintain hierarchical relationships, with the purpose of provoking scholars in the field of hate studies to reflect on its scope.